Climate litigation against companies - Weller, Marc-Philippe; Tran, Mai-Lan (Climate action, 2022)
The article takes the spectacular Shell ruling from The Hague as an opportunity to identify cross-jurisdictional problems of civil climate change litigation. The Shell case was the first climate action between private parties that was successful in the first instance and led to Shell’s obligation to drastically reduce its greenhouse gas emissions, including its Scope 3 emissions. From the perspective of legal realism, the Dutch ruling provides a momentum for climate litigation world‑wide. However, from the perspective of potential lawsuits for the reduction of C O2 emissions against companies in Germany, one must assert that the Shell ruling cannot simply be transposed into the German legal order.
Gesehen am 16.08.2023